Redesign the fuel tank of water vehicle to improve its stability / Abdul Razak Laulang, Mahani Ibrahim and Sazri Azam Roslan - Laulang, Abdul Razak; Ibrahim, Mahani; Roslan, Sazri Azam (Faculty of Mechanical Engineering, 1997)
The objective of our final project is to design the fuel tank of water vehicle to improve its stability. In our design we will do an analysis and calculation to find the suitable fuel tank which can improve the water vehicle stability. Our design is based on the water vehicle that we have choose. From the data which we get from this water vehicle, we will design and find the suitable fuel tank that can improve the water vehicle stability. In this project, we have choose the ship which is aluminium patrolvessel ship.